Legal Regulation of Collective Bargaining in the Ontario Public Sector - Carter, D. (Relations industrielles / Industrial Relations, 1974)
In this paper, the author describes the major features of the legal structure for collective bargaining in the Ontario public sector. The emphasis is mostly placed upon the Crown Employees Collective Bargaining Act which applies to a sub-stantial portion of the Ontario public sector labor force. The basic issues dealt with include : disputes settlement, scope of bargaining, determination of bargaining units, representation elections and political activities.